OPTIMASI KAPASITAS PRODUKSI UKM DENGAN GOAL PROGRAMMING - Welly Sugianto (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
UKM Jovelyn is a small medium enterprise (SME) that engaged in the field of bakery production. Until now, they produce cakes and cookies. They sell products throughout the Batam area which includes (Tiban market, aviari market, mitra market and puja bahari market), shops, school canteens and so on. The SME targets several things such as profit per month, number of hours worked, number of overtime hours, machine utilities, labor utilities and so forth. Until now, the SME has not been able to reach the targets because the UKM has not determined the production amount based on the appropriate calculation. The number of products made is determined only on an intuitive basis. Determination of the amount of production cannot be determined by the usual simplex method because the objective function in the usual simplex method contains a target. Problem solving is done by using goal programming. The results of the calculation analysis show that to achieve the optimal value, the SME must produce coconut root cookies, butter cookies, nastar cookies, snow princess cookies and peanut cookies respectively 11.89 kg, 22.43 kg, 24.96 kg , 1.97kg and 0 kg. Sensitivity analysis is carried out after there are changes in conditions that result in changes in the linear program matrix, so the number of products that must be made also changes which include coconut root cookies as much as 12.8 kg, as much as 16.91 kg of butter cookies, nastar cookies as much as 25.7 and the last is 3.39 kg of nut cookies which in the initial calculation, nut cookies were not produced. The sensitivity analysis is not done by recalculation but rather by modifying the matrix and completing iteration with primal dual.